CO substitution by PPh3 in Fe2S2(CO)6 proceeds via a novel Fe2S intermediate. Issue 41 (23rd April 2021) - Zhang, Fanjun; Woods, Toby J.; Rauchfuss, Thomas B.; Arrigoni, Federica; Zampella, Giuseppe
Abstract : Substitution of CO ligands by PPh3 in Fe2 (μ-S2 )(CO)6 proceeds by a desulfurization–resulfurization sequence, generating SPPh3 and Fe2 (μ-S)(CO)6 (PPh3 )2 as intermediates. Protonation of Fe2 (μ-S)(CO)6 (PPh3 )2 occurs at sulfur. Abstract : The reaction of Fe2 S2 (CO)6 and PPh3 affords Fe2 S2 (CO)4 (PPh3 )2 by an unprecedented mechanism involving the intermediacy of SPPh3 and Fe2 S(CO)6 (PPh3 )2 .